Your creative career : turn your passion into a fulfilling and financially rewarding lifestyle - Sabino, Anna (Career Press, 2017)
Anna Sabino is an artist, but certainly not a starving one. She wasn't born into a wealthy family, didn't inherit money from a distant relative, and doesn't have a rich husband. But she made it as an entrepreneur, as a single woman, and most important, as an artist. In Your Creative Career, she shows her fellow artists and creatives how to build a business that reflects their talent and true calling while generating serious cash. Whether the goal is to build an empire and be financially free, create a lifestyle business, or just to have more time, Your Creative Career guides you through every aspect of creative entrepreneurship. If you want to start your creative career, transition into it, or give it a boost, this book is a must read that features: Proven systems and strategies to create ideally priced products that keep selling. The importance of going through all the steps of making it from idea inception and execution to branding and distribution. The importance of transitioning from artistic solitude to collaborative, creative entrepreneurship. The most effective marketing and PR methods adjusted to the new reality of short attention spans and information overload.